Clinical, epidemiological, and genomic evidence on mpox in mainland China, 2022–2025: a scoping review - Yanjie Peng; Yun Geng; Fan Yang; Ting Yang (Frontiers in Microbiology, 2026)
Background Since 2022, mpox has expanded globally with sustained human-to-human transmission and increasing evidence of MPXV genomic diversification. In mainland China, mpox evidence has accumulated rapidly, but clinical, epidemiological, and genomic findings remain fragmented. Methods We conducted a scoping review of PubMed, CNKI, and WanFang databases up to March 2, 2026, and integrated literature-derived evidence with public MPXV sequences from GenBank, GenBase, and GISAID. Literature-derived data were used to map clinical-epidemiological characteristics, study-level genomic evidence, sequencing coverage, and reported lineage distribution. Curated public MPXV sequences were used for phylogenetic reconstruction, amino acid mutation profiling, and APOBEC-like substitution analysis. Results Fifty-eight studies were included: 32 addressed clinical or epidemiological evidence only, 25 addressed genomic evidence only, and one contributed to both domains. Fourteen hospital-based studies summarized 951 cases, showing that reported cases were concentrated among young adult men, with frequent MSM exposure (798/897, 89.0%; 95% CI 86.7–90.9%) and HIV co-infection (469/951, 49.3%; 95% CI 46.1–52.5%). Public sequence curation identified 231 unique mainland China MPXV sequences, of which 230 were used for phylogenetic and mutation analyses. Literature-based genomic evidence comprised 26 genomic studies, 37 study-level genomic records, and 31 reported-case units, including 414 sequenced cases among 530 reported cases (78.1%; 95% CI 74.4–81.4%). Clade IIb predominated among sequenced cases (412/414, 99.5%; 95% CI 98.3–99.9%), with C.1.1 and C.1 most frequently represented. Within the available dataset, public genomes represented multiple lineages and were unevenly distributed across regions and time. Mutation analysis revealed dispersed amino acid variation and a predominance of G>A and C>T transitions (73.0%). After collapsing recurrent substitutions to unique genomic sites, the proportion of G>A/C>T transitions decreased to 35.8% and further to 17.8% under a strict APOBEC3 motif definition, indicating that the observed mutation spectrum includes both shared lineage-associated substitutions and sequence-context-based APOBEC-like patterns. Conclusion Available evidence indicates multi-lineage MPXV circulation and in mainland China, but interpretation remains constrained by uneven sequencing and lack of individual-level clinical-genomic linkage. Integrated genomic surveillance and standardized data linkage are needed to better characterize MPXV transmission and evolution.